Aislamiento y caracterización de un péptido antibacteriano del veneno de Centruroides margaritatus - Rivera, Carlos (2010)
In this work, from the venom of Centruroides margaritatus (Gervais, 1841) (Scorpiones, Buthidae), one peptide with antibacterial activity was isolated and characterized. This peptide was isolated from 50 mg of whole venom, the purification was initially performed by chromatography on CM-Sephadex C-25 obtaining protein peaks seven. The peak III of this separation was purified by gel filtration on Sephadex G-75, yielding protein peaks two, the second of which proved to be the antibacterial peptide. This peptide represents about 3 % of whole venom protein and by PAGE-SDS, was determinate it has 7,3 kDa of molecular weight. The antibacterial peptide inhibits the growth of Bacillus cereus, Staphylococcus aureus, Pseudomonas aeruginosa y Serratia marcencens, in microplates with minimal media Davies, but in assays in Muller-Hinton agar, showed no significant inhibition halos; concluding that peptide has bacteriostatic activity but not bactericidal activity. In addition has not activity on Enterococcus faecalis, Escherichia coli, Salmonella choleraesuis and Klebsiella pneumoniae. Antibacterial peptide also inhibited the growth of Aspergillus níger and Candida albicans during 48 hours, but has not hemolytic activity.